Bioethics as a support for biosecurity - Irribarra Mengarelli, Roberto R. (Acta Bioethica, 2006)
Bio security norms imply an additional cost that has to be managed by the dentist-surgeon. In a market economy, where price is the principal comparison factor for the choice of a provider, a new item leaves the responsible provider in disadvantage facing those who don't consider these standards. The impossibility to exert a strict control on effective bio-security rules demonstrates that bioethics plays a vital rôle backing odontological service.